Positive fungal interactions are key drivers in Antarctic endolithic microcosms at the boundaries for life sustainability - Biagioli, Federico; Coleine, Claudia; Buzzini, Pietro; Turchetti, Benedetta; Sannino, Ciro; Selbmann, Laura (FEMS Microbiology Ecology, 2023)
In the ice-free areas of Victoria Land in continental Antarctica, where the conditions reach the limits for life sustainability, highly adapted and extreme-tolerant microbial communities exploit the last habitable niches inside porous rocks (i.e. cryptoendolithic communities). These guilds host the main standing biomass and principal, if not sole, contributors to environmental/biogeochemical cycles, driving ecosystem processes and functionality in these otherwise dead lands. Although knowledge advances on their composition, ecology, genomic and metabolic features, a large-scale perspective of occurring interactions and interconnections within and between endolithic fungal assemblages is still lacking to date. Unravelling the tight relational network among functional guilds in the Antarctic cryptoendolithic communities may represent a main task. Aiming to fill this knowledge gap, we performed a correlation-network analysis based on amplicon-sequencing data of 74 endolithic microbiomes collected throughout Victoria Land. Endolithic communities' compositional pattern was largely dominated by Lichenized fungi group (83.5%), mainly represented by Lecanorales and Lecideales, followed by Saprotrophs (14.2%) and RIF+BY (2.4%) guilds led by Tremellales and Capnodiales respectively. Our findings highlighted that fungal functional guilds' relational spectrum was dominated by cooperative interactions led by lichenised and black fungi, deeply engaged in community trophic sustain and protection, respectively. On the other hand, a few negative correlations found may help in preserving niche boundaries between microbes living in such strict spatial association.Fungal interactions promote the functioning of Antarctic endolithic communities.